Curricular Issues in School Education: Critical Analysis of Understanding about the Implemented Curriculum - Mishra, Nirmal Raj (Rupantaran: A Multidisciplinary Journal, 2020)
This paper focus on exploring the curricular issues viz. subject matter, pedagogy and assessment process of implemented / taught curriculum in school education. Similarly, the teachers’ understandings are key areas to find out the issues in education that are guiding engine to operate schools’ education efficiently. During this study course, it adopted the descriptive as well as phenomenological methodology on the basis of educational literature, own experience and group discussion with selected teachers. The dilemma about curricular components has created the new discourse in school education today. Moreover, the challenges to improve the elaborated isueses are crucial problems for teachers in enhancing quality teaching learning skills